Influence of Diazotrophic Bacteria on Antioxidant Enzymes and Some Biochemical Characteristics of Soybean Subjected to Water Stress - Hamed Zakikhani; Mohammad Reza Ardakani; Farhad Rejali; Majid Gholamhoseini; Aydin Khodaei Joghan; Aria Dolatabadian (Journal of Integrative Agriculture)
Drought stress is an abiotic stress that imposes serious constraints on plants. The present investigation was carried out to determine the inter-relationship between some physiological attributes of soybeans affected by drought stress and pure isolates of Azotobacter and Azospirillum. Drought stress and bacterial application increased catalase and glutathione peroxidase activity, whereas drought stress increased superoxide dismutase activity during the pod-filling stage. Abscisic acid and proline levels increased due to drought stress and bacterial application during the flowering stage, whereas total plant nitrogen was enhanced under well-watered conditions when plants were inoculated with bacteria. The close relationship between enzyme activity and drought stress with bacteria indicated that antioxidant enzymes play an important role in alleviating the detrimental effects of water stress. In addition, the enhancement of abscisic acid and proline could be positively linked with drought stress, and drought-induced abscisic acid could induce proline accumulation and the expression of antioxidant enzyme genes.